Temp Nations? A Research Agenda on Migration, Temporariness, and Membership. (August 2019) - Cook-Martín, David
This article outlines a research agenda to study how, why, and with what consequences systems of migration policy that rely on time-delimited statuses have been tools of nation-state making. Taking a long view and comparing key contemporary cases, I argue that temporary migration regimes have been appealing because they purport to reconcile the disparate interests and preferences of political actors in sending and receiving countries, native and foreign workers, and employers. Such regimes have been a means for the affirmative selection of migrants as workers—an approach that preserves the option of rejecting them as permanent members. The proposed research would uncover the full range of temporal means by which states have shaped populations through migration policy. Substantively, it explores how changes in the ratio of temporary to permanent statuses affect the meaning of political belonging. This would include an examination of how the policing of temporariness requires routine bureaucratic monitoring as well as extreme measures like deportation with consequences for migrants as well as for the communities in which they live.